Exploring the influence of iron doping on structural, morphological, and optical properties of spin-coated tin sulphide thin films for optoelectronic applications - Karimunnesa, Syeda; Rahman, Md Ashiqur; Jania, Rutaba; Esha, I N; Bashar, M S; Hussain, Kazi Md Amjad; Maria, Kazi Hanium (Bangladesh Journal of Physics, 2025)
Undoped and iron (Fe) doped tin sulphide (SnS) thin films with different contents (0, 5, 7, and 9 %) were deposited on a glass substrate at 350 °C by the spin coating method. In this work, the effect of Fe doping on the structural, morphological, optical, and dielectric characteristics of the SnS films were analyzed using X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, Scanning electron microscopy (SEM), and UV–Vis–NIR spectroscopy. XRD patterns confirm the orthorhombic crystal structure with a (111) preferential orientation for all the prepared samples. Structural studies further explored the decrease in crystallite size due to the inclusion of Fe doping in SnS.. Based on the FT-IR results, a minor stretching vibration in Sn-S modes was observed in undoped SnS and Fe-doped SnS samples. SEM study showed that the grain size decreases with the increased doping concentration of Fe. Optical results revealed an increasing trend of bandgap from 3.1 eV to 3.23 eV with the doping of Fe at various concentrations. The results indicate that the synthesized Fe-doped SnS thin films exhibit potential for applications in photovoltaic and optoelectronic devices. Bangladesh Journal of Physics, Vol. 32, Issue 1, pp. 21 – 32, June 2025